2011
DOI: 10.1016/j.jmii.2011.01.025
|View full text |Cite
|
Sign up to set email alerts
|

Viral etiology of acute lower respiratory tract infections in hospitalized young children in Northern Taiwan

Abstract: RSV is the most common pathogen causing LRTIs in young children, followed by hMPV. The hMPV group had higher mixed infection rate than RSV group. hBoV does circulate in northern Taiwan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 31 publications
(38 reference statements)
1
27
0
Order By: Relevance
“…These concentrated antibodies display higher functional potency than native preparations. Mixed types of infections are common in children infected with RSV [24]. MAbs that are highly specific for RSV cannot control mixed infections in susceptible patients.…”
Section: Resultsmentioning
confidence: 99%
“…These concentrated antibodies display higher functional potency than native preparations. Mixed types of infections are common in children infected with RSV [24]. MAbs that are highly specific for RSV cannot control mixed infections in susceptible patients.…”
Section: Resultsmentioning
confidence: 99%
“…There may be several reasons for the difference in findings including the type of diagnostic assays used and the detection of various respiratory targets, clinical setting, patient age, and timing of specimen collection. Many studies have focused on populations mostly consisting of hospitalized pediatric patients and these studies have shown that RSV was the leading pathogen identified in these young children who were between 16 months to 14 years old [21,22,23]. In contrast, our study examined all age groups, including community-based and hospital-based specimens.…”
Section: Resultsmentioning
confidence: 99%
“…The specimens were preserved in standard transport media and were inoculated on four cell lines (MRC-5 from fibroblast of human fetal lung, Hep-2, A549 from laryngeal carcinoma, and RD cell from rhabdomyosarcoma) for isolation of respiratory viruses. Those culture exhibiting RSV specific cytopathological effects were confirmed by reactions with immunofluorescent antibodies and were stored at −80°C [4].…”
Section: Methodsmentioning
confidence: 99%